Alternative Object Use in Adults and Children: Embodied Cognitive Bases of Creativity - Gubenko, Alla; Houssemand, Claude (Frontiers in Psychology, 2022)
Why does one need creativity? On a personal level, improvisation with available resources is needed for online coping with unforeseen environmental stimuli when existing knowledge and apparent action strategies do not work. On a cultural level, the exploitation of existing cultural means and norms for the deliberate production of novel and valuable artifacts is a basis for cultural and technological development and extension of human action possibilities across various domains. It is less clear, however, about how creativity develops and how exactly one arrives at generating new action possibilities and producing multiple alternative action strategies using objects. In this theoretical paper, we first consider existing accounts of the creative process in the Alternative Uses Task and then present an alternative interpretation, drawing on sociocultural views and an embodied cognition approach. We explore similarities between the psychological processes underlying the generation of new uses in the Alternative Uses Task and children’s pretend play. We discuss possible cognitive mechanisms and speculate how the generation of new action possibilities for common objects in pretend play can be related to adults’ ability to generate new action strategies associated with tool use. Implications for creativity development in humans and embodied artificial agents are discussed.